Выстрел на перевале: [роман] / Борис Бабкин - Бабкин Борис Николаевич
Экземпляры: аб. (2009) / Инвентарный номер: 52806 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Б 12 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44